2021
DOI: 10.1002/advs.202102495
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Electron Transfer in Nanostructured Electrodes Improves the Sensitivity of Electrochemical Biosensors

Abstract: Electrochemical biosensors hold the exciting potential to integrate molecular detection with signal processing and wireless communication in a miniaturized, low-cost system. However, as electrochemical biosensors are miniaturized to the micrometer scale, their signal-to-noise ratio degrades and reduces their utility for molecular diagnostics. Studies have reported that nanostructured electrodes can improve electrochemical biosensor signals, but since the underlying mechanism remains poorly understood, it remai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…Signal gain is the baseline-subtracted ratio between the SWV peak generated in the presence of the target molecule to that produced in the absence of target; we used this value to quantify analyte concentrations in the sample. 3,19,33 We found that the signal gain produced by 10 μM DOX (the maximum clinically relevant concentration) increased by ∼36% on the C6-OH SAM relative to the C6-COOH SAM—from 129% to 176% ( Fig. 2A , upper plot).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Signal gain is the baseline-subtracted ratio between the SWV peak generated in the presence of the target molecule to that produced in the absence of target; we used this value to quantify analyte concentrations in the sample. 3,19,33 We found that the signal gain produced by 10 μM DOX (the maximum clinically relevant concentration) increased by ∼36% on the C6-OH SAM relative to the C6-COOH SAM—from 129% to 176% ( Fig. 2A , upper plot).…”
Section: Resultsmentioning
confidence: 95%
“…There have been many innovations in selecting high-affinity aptamers using directed evolution, [11][12][13][14] and also in improving the signaling of these aptamers by rationally designing switches 15,16 and engineering electrode interfaces to tune transduction. [17][18][19][20][21] However, one major challenge is that these sensors often suffer from poor specificity, such that the presence of structurally-similar interferents and metabolites can potentially make accurate molecular quantification of the target difficult or impossible. This is because the specificity of molecular detection is heavily dependent on the aptamer's capacity to discriminate between chemically similar targets, and it can be exceedingly difficult to generate aptamers that exhibit such excellent selectivity while also achieving a robust target-induced conformational change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that nanoporous structured electrodes offer greatly improved electrochemical detection sensitivity relative to planar electrodes, with a higher SNR due to reduced charge screening effects ( 38 ). This enhanced sensitivity is important in this context, because in vivo experiments intrinsically have high background noise.…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 , 8 , 91 , 92 , 93 ] To improve the sensitivity of biosensors, a variety of strategies have been raised to amplify signals, such as enzymatic reactions, DNA nanotechnology, and so on. [ 94 , 95 ] Among them, DNA walker‐based biosensors exhibit superior performance in biosensing. The programmability of DNA nanotechnology enables the design of walking behaviors that specifically respond to different biological targets.…”
Section: Dna Walkers‐based Biosensorsmentioning
confidence: 99%